Modification of epoxy resin by polysulfone to improve the interfacial and mechanical properties in glass fibre composites. II. Adhesion of the epoxy-polysulfone matrices to glass fibres - Brantseva, Tv.; Gorbatkina, Y.A; Mader, E.; Dutschk, V.; Kerber, M.L.
Adhesion of epoxy-polysulfone (PSF)matrices to glass fibres of 12-30 ìm in diameter was studied under both quasi-static and cyclic loadings. A pull-out technique was used for adhesion measurement. It was shown that incorporation of PSF into epoxy resin changed its adhesion to fibres. A maximum was observed in the adhesion strength vs. PSF content dependence at 10 wt
Keywords: EPOXY-POLYSULFONE MATRICES; ADHESION STRENGTH; PULL-OUT TEST; QUASI-STATIC LOADING; CYCLIC LOADING